2018
DOI: 10.1016/j.jds.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different preventive agents on initial occlusal and proximal caries lesions: A follow-up study

Abstract: Background/purpose Monitoring the effects of different caries-preventive agents on initial caries lesions in orthodontic patients is important. Therefore, the purpose of this study is to investigate the efficacy of different preventive methods in preventing occlusal and proximal incipient lesions (ILs) during fixed orthodontic treatment. Materials and methods Forty-eight subjects at the beginning of fixed orthodontic treatment were included. All subjects were well educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For the first time, such a guided enamel regeneration enables the tooth to get closer to its healthy state and further from the disease state 3,26 . Arresting a lesion with fluoride stops the imminent clinical issue at hand, but does little to alleviate the thread of a lesion becoming active again and progressing to a cavity 27 .…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, such a guided enamel regeneration enables the tooth to get closer to its healthy state and further from the disease state 3,26 . Arresting a lesion with fluoride stops the imminent clinical issue at hand, but does little to alleviate the thread of a lesion becoming active again and progressing to a cavity 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical characterization of proximal carious lesions is scarce in the literature. The susceptibility of different tooth surfaces for caries development and progression is markedly differed in occlusal versus smooth surfaces [ 21 ], added to differences in the inflammatory pulp response in proximal lesions as compared to occlusal lesions [ 22 ]. This might necessitate an assessment of the structural changes in proximal carious lesions in comparison to occlusal in the same tooth model.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, the evidence has reported that 1% CHX gel significantly reduces root caries lesions [45, 46]. Moreover, it has even been recommended for root caries in patients requiring special care [44], such as institutionalized elderly people, as it can control established root lesions and reduce the incidence of new lesions [45].…”
Section: Discussionmentioning
confidence: 77%
“…Another noninvasive product for topical use as a preventive method for root caries is 1% chlorhexidine gel (CHX). Evidence shows that CHX can inhibit the growth of cariogenic bacteria on the root surface [39][40][41][42][43], specifically on S. mutans [44], reducing root caries lesions [45,46], and even as a tertiary preventive method, showing favorable results [45,47,48].…”
Section: Introductionmentioning
confidence: 99%